2014
DOI: 10.1128/aem.01139-14
|View full text |Cite
|
Sign up to set email alerts
|

The Cry Toxin Operon of Clostridium bifermentans subsp. malaysia Is Highly Toxic to Aedes Larval Mosquitoes

Abstract: The management and control of mosquito vectors of human disease currently rely primarily on chemical insecticides. However, larvicidal treatments can be effective, and if based on biological insecticides, they can also ameliorate the risk posed to human health by chemical insecticides. The aerobic bacteria Bacillus thuringiensis and Lysinibacillus sphaericus have been used for vector control for a number of decades. But a more cost-effective use would be an anaerobic bacterium because of the ease with which th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…The binary and quaternary cytolytic complexes of bacterial origin where aegerolysin-like proteins are combined with larger, non-aegerolysin protein partner(s) that have been described to date comprise: Cry16Aa/Cry17Aa/Cbm17.1/Cbm17.2 from Clostridium bifermentas subsp. Malaysia 41 ; Cry34Ab1/Cry35Ab1 from B. thuringiensis 42,43 ; and AflP-1A/AflP-1b from A. faecalis 23 . These heteromeric aegerolysin-based cytolytic complexes have been exploited as potent biopesticides for specific pests, whereby Cry16Aa/Cry17Aa/Cbm17.1/Cbm17.2 acts against Aedes mosquitoes, and Cry34Ab1/Cry35Ab1 and AflP-1A/AflP-1b act against coleoptera species, and mainly WCR.…”
Section: Introductionmentioning
confidence: 99%
“…The binary and quaternary cytolytic complexes of bacterial origin where aegerolysin-like proteins are combined with larger, non-aegerolysin protein partner(s) that have been described to date comprise: Cry16Aa/Cry17Aa/Cbm17.1/Cbm17.2 from Clostridium bifermentas subsp. Malaysia 41 ; Cry34Ab1/Cry35Ab1 from B. thuringiensis 42,43 ; and AflP-1A/AflP-1b from A. faecalis 23 . These heteromeric aegerolysin-based cytolytic complexes have been exploited as potent biopesticides for specific pests, whereby Cry16Aa/Cry17Aa/Cbm17.1/Cbm17.2 acts against Aedes mosquitoes, and Cry34Ab1/Cry35Ab1 and AflP-1A/AflP-1b act against coleoptera species, and mainly WCR.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Clostridium bifermentans subsp. malaysia is active against a host of mosquito genera, especially Anopheles, a carrier of malarial parasites (24,25).…”
mentioning
confidence: 99%
“…Cry23 associates with Cry37, forming a binary toxin (PDB code 4RHZ) that shows pore formation activity (21). Other examples of Cry proteins that are expressed in the same operon with additional proteins are the Cry16 and Cry17 proteins, which are expressed with two additional proteins named Cbm17.1 and Cbm17.2 in Clostridium bifermentans (22). It was shown that individual Cry16 and Cry17 proteins are not active against mosquitoes, while mosquitocidal activity was observed when the four proteins were expressed together, indicating that the four proteins are required for toxicity against Aedes aegypti (22).…”
Section: Discussionmentioning
confidence: 99%
“…Other examples of Cry proteins that are expressed in the same operon with additional proteins are the Cry16 and Cry17 proteins, which are expressed with two additional proteins named Cbm17.1 and Cbm17.2 in Clostridium bifermentans (22). It was shown that individual Cry16 and Cry17 proteins are not active against mosquitoes, while mosquitocidal activity was observed when the four proteins were expressed together, indicating that the four proteins are required for toxicity against Aedes aegypti (22). At the primary sequence level, the Cry-ETX/MTX toxins share limited identity, but at the structural level, all of these proteins showed significant similarities to proteins from the aerolysin-like ␤-PFT group.…”
Section: Discussionmentioning
confidence: 99%